Transformasi Digital dalam Pemasaran: Strategi Efektif untuk Meningkatkan Penjualan Produk Olahan Teri Nasi di Desa Padelegan - Rahayu, Runik Puji; Fitrianti, Rani Nur; Syahadatina, Rika; Djaja, Mohamad Herman (Assyarikah: Journal of Islamic Economic Business, 2024)
This study aims to analyze the effect of digital marketing strategies on increasing sales of local anchovy rice food products for micro, small, and medium enterprises (MSMEs) in Padelegan Village. Digital marketing strategies are becoming an increasingly popular approach among MSMEs to expand their market reach and increase sales volume. Especially in the context of villages, the use of digital technology provides significant potential to connect MSMEs with potential consumers, both domestically and abroad. This study uses a quantitative survey approach that allows for empirical data on digital marketing practices and their impact on MSME sales performance. Questionnaires were distributed to a number of respondents, namely MSMEs who produce and market local products in the form of processed anchovies in Padelegan Village. The data collected through this questionnaire were analyzed using regression analysis to identify significant relationships between digital marketing strategy variables as independent variables and increased sales as dependent variables. This study also considers dimensions of digital marketing strategies such as the use of social media, paid advertising, and search engine optimization (SEO) which have been shown to have a significant role in attracting new customers and retaining existing customers. The results of this study are expected to provide a deeper understanding of the effectiveness of digital marketing in supporting the growth of local product sales, especially for MSMEs operating in rural areas. These findings are not only relevant for business actors in Padelegan Village but are also useful as a reference for MSME actors in other areas with similar conditions who want to optimize their digital marketing strategies to increase competitiveness in an increasingly competitive market (Doe, 2023). In addition, the results of this study are expected to be a basis for policy makers in developing training and empowerment programs for MSMEs in the field of digital marketing, thereby supporting local economic resilience in the future. By combining empirical perspectives on digital marketing and its impact on sales, this study provides a significant academic contribution to the digital marketing literature in the MSME sector.